2017
DOI: 10.1016/j.aca.2017.04.043
|View full text |Cite
|
Sign up to set email alerts
|

Electrosynthesized molecularly imprinted polyscopoletin nanofilms for human serum albumin detection

Abstract: Molecularly imprinted polymers (MIPs) rendered selective solely by the imprinting with protein templates lacking of distinctive properties to facilitate strong target-MIP interaction are likely to exhibit medium to low template binding affinities. While this prohibits the use of such MIPs for applications requiring the assessment of very low template concentrations, their implementation for the quantification of high-abundance proteins seems to have a clear niche in the analytical practice. We investigated thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
54
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 79 publications
(55 citation statements)
references
References 43 publications
1
54
0
Order By: Relevance
“…Using the nanolithography mode of AFM we found that the thickness increased from 7.9±0.2 nm for the polyscopoletin layer (without Pdx peptide SAM) via 9.2±0.4 nm for the NIP (with underlying Pdx peptide SAM) to 10.4±0.5 nm for the VIP nanofilms (with underlying P450cam template anchored to the Pdx peptide SAM). These results support the nanometer‐scale control over the film thickness and they are close to the values of other electrosynthesized polyscopoletin films ,,…”
Section: Resultssupporting
confidence: 85%
“…Using the nanolithography mode of AFM we found that the thickness increased from 7.9±0.2 nm for the polyscopoletin layer (without Pdx peptide SAM) via 9.2±0.4 nm for the NIP (with underlying Pdx peptide SAM) to 10.4±0.5 nm for the VIP nanofilms (with underlying P450cam template anchored to the Pdx peptide SAM). These results support the nanometer‐scale control over the film thickness and they are close to the values of other electrosynthesized polyscopoletin films ,,…”
Section: Resultssupporting
confidence: 85%
“…Whilst thicker films lead to higher loading of the template molecule, thinner films are less stable. However, templates can be easily removed from the thin films …”
Section: Resultsmentioning
confidence: 99%
“…As a compromise between the lower stability of thin layers and the restriction of target accessibility with increasing film thickness, 10 cyclic voltammetry scans were chosen for the preparation of laccase‐imprinted sensor (Figure ) …”
Section: Resultsmentioning
confidence: 99%
“…An example is the development of a polyscopoletinbased MIP nanofilm for the electrochemical determination of elevated human serum albumin (HSA) in urine. The results suggest that MIP-based sensors may be applicable for quantifying high-abundance proteins in a clinical setting [25].…”
Section: Molecularly Imprinted Polymer (Mip) Sensorsmentioning
confidence: 94%